2013
DOI: 10.2146/ajhp120457
|View full text |Cite
|
Sign up to set email alerts
|

Association between caffeine citrate exposure and necrotizing enterocolitis in preterm infants

Abstract: Cumulative exposure to caffeine citrate among infants who developed NEC and infants who did not develop NEC differed significantly at only one of six evaluated time points during the seven days before NEC development or the index date. There was no significant difference between groups in the proportions of patients who received caffeine citrate or in mean serum caffeine concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
1
11
1
2
Order By: Relevance
“…Data reported by the German Neonatal Network suggest that surgical procedures for NEC are more likely in infants receiving caffeine citrate (3 vs. 1.3%), but the gestational age in these two groups differed by as much as 2 weeks (mean gestational age in the caffeine group: 28.4 weeks, without caffeine: 30.5 weeks; W. Goepel, personal communication, May 2013). In a recent case-control study, no increased risk of NEC was observed in infants receiving caffeine citrate [13]. Our study shows that NEC was less likely with LP than with ECC, but this result has to be viewed with caution as this was not a randomized controlled trial and we cannot rule out that other changes in management had occurred contributing to a fall in the NEC rate.…”
Section: Discussioncontrasting
confidence: 56%
“…Data reported by the German Neonatal Network suggest that surgical procedures for NEC are more likely in infants receiving caffeine citrate (3 vs. 1.3%), but the gestational age in these two groups differed by as much as 2 weeks (mean gestational age in the caffeine group: 28.4 weeks, without caffeine: 30.5 weeks; W. Goepel, personal communication, May 2013). In a recent case-control study, no increased risk of NEC was observed in infants receiving caffeine citrate [13]. Our study shows that NEC was less likely with LP than with ECC, but this result has to be viewed with caution as this was not a randomized controlled trial and we cannot rule out that other changes in management had occurred contributing to a fall in the NEC rate.…”
Section: Discussioncontrasting
confidence: 56%
“…62 Necrotizing enterocolitis Retrospective studies have reported conflicting results regarding a potential association between caffeine treatment and necrotizing enterocolitis (NEC). 63,64 A post hoc analysis from a trial of caffeine therapy for AOP showed a trend toward more NEC in the caffeine compared with the placebo-treated group. 65 Importantly, however, the randomized CAP Trial observed no differences in the rates of NEC between the treatment groups (6.3% caffeine group, 6.7% placebo group, p = 0.63).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…A retrospective analysis of an association between caffeine and necrotizing enterocolitis (NEC) can be conducted in a few months using a neonatal intensive care unit (NICU) database with minimal expense. (6)…”
Section: Introductionmentioning
confidence: 99%